Molecular subtyping of hypertensive disorders of pregnancy - Michal A. Elovitz; Elaine P. S. Gee; Nathaniel Delaney-Busch; Alison B. Moe; Mitsu Reddy; Arkady Khodursky; Johnny La; Ilma Abbas; Kay Mekaru; Hunter Collins; Farooq Siddiqui; Rory Nolan; et al. (Nature Communications)
Abstract Hypertensive disorders of pregnancy (HDP), including preeclampsia, affect 1 in 6 pregnancies, are major contributors to maternal morbidity and mortality, yet lack precision medicine strategies. Analyzing transcriptomic data from a prospectively-collected diverse cohort (n = 9102), this study reveals distinct RNA subtypes in maternal blood, reclassifying clinical HDP phenotypes like early/late-onset preeclampsia. The placental gene PAPPA2 strongly predicts the most severe forms of preeclampsia in individuals without pre-existing high risk factors, months before symptoms, and its overexpression correlates with earlier delivery in a dose-dependent manner. Further, molecular subtypes characterized by immune genes are upregulated in less severe forms of HDP. These results reclassify HDP clinical phenotypes into two distinct molecular subtypes, placental-associated or immune-associated. Validation performance for placental-associated HDP yields an AUC of 0.88 in the advanced maternal age population without pre-existing high risk factors. Molecular subtypes create new opportunities to apply precision-based medicine in maternal health.